Orthodox Perspectives on Mission - Vassiliadis, Petros (Book collections on Project MUSE., 2013)
Orthodox Perspectives on Mission is a humble tribute to some great Orthodox theologians, who in the past have provided substantial contribution to contemporary missiological and ecumenical discussions, and at the same time an Orthodox contribution to the upcoming 2013 Busan WCC General Assembly, continuing a long history of similar contributions by the Orthodox before each major ecumenical event. The collected volume is divided into two parts: Part 1, under the subtitle "The Orthodox Heritage," consists of a limited number of representative Orthodox missiological contributions of the past, whereas Part 2 includes all the papers presented in the Plenary of the recent Edinburgh 2010 conference, as well as the short studies and contributions prepared during the Edinburgh 2010 ongoing study process.